PENGARUH PROPORSI KOMISARIS INDEPENDEN, FREE CASH FLOW , ROA DAN PERPUTARAN ASET TERHADAP PRAKTEK MANAJEMEN LABA PADA PERUSAHAAN SEKTOR TAMBANG BATU BARA - RACHMAN, TAUFIQUR (Jurnal Akuntansi AKUNESA, 2015)
The aim in this research was to examine the influence of ,free cash flow, ROA , proportion of independent commissioner and turn over asset on the performance of detection practices of management relation with the earnings management. Discretionary accruals are used as a proxy for earnings management. This research used 11 coal companies listed in Indonesia Stock Exchange, selected using purposive sampling method, during the research period 2012-2014. Data were analyzed using simple regression method. Based on test results concluded that asset turnover and free cash flow has significant effect on earnings management. While OA and the proportion of independent commissioner has no significant effect on earnings management. This means that companies with high asset turnover and high free cash flow that will restrict earnings management practice.Keywords: earnings management, cash flow, assets turnover, ROA, independent commissioner